Efficacy of water conservation measures in coconut plantations to enhance ground water resource and coconut yield in West Coast region - Manoj P. Samuel, A.C. Mathew, C. Thamban and (Journal of Plantation Crops, 2018)
Efficacy of water conservation measures in coconut plantations to augment ground water resource and coconut yield in the West Coast region was studied by implementing two conservation measures, half moon bund and trench, in coconut gardens. Impact of these conservation measures was studied by monitoring the amount of water conserved by these structures and the improvement in the coconut yield due to these interventions. An attempt was also made to study the contribution of the conserved water in increasing the local ground water resource by monitoring the yield of ‘Surangams’, an indigenous water harnessing structure, that draws water from unconfined aquifer in the hillock where the water conservation measures were undertaken. The conservation measures were taken up in a total area of 17,200 m2 in the coconut gardens of nine farmers and two control plots also was selected having a total area of 4900 m each having one Surangam in their respective catchment area. The study revealed that a positive correlation exists between the rainfall and water conserved. However, the amount varied from plot to plot. This variation is mainly due to the non uniformity of the catchment areas, mainly the size of catchment and nature of water conservation structure. Average amount of rain/runoff water collected in plots where a combination of half-moon bund and trench were taken up in the coconut gardens was 51 m 3 per year. This was only 30 m and 27 m when half-moon bund and trench alone was taken up. There was only a meagre improvement in the annual Surangam yield due to the conserved water. However, the improvement was more noticeable (13%) during the non-rainy season, December to May. The plots where two conservation structures, half-moon bund and trench together, were taken up showed 58 per cent increase in the yield of coconut. Coconut yield increased by 37 and 29 per cent where only one conservation structure was taken up, i.e., half-moon bund and trench, respectively. During the same period, average coconut yield in the control plots was decreased marginally from 61 to 56 nuts per palm per year. This shows the possibility of conserving water and enhancing the productivity of coconut in rain fed area by adopting water conservation measures in the hilly region of West Coast. The fact that majority of the coconut cultivation in this region is still under rain fed condition adds to the significance of the result.